PERLINDUNGAN HUKUM TERHADAP PENGGUNA SISTEM PEMBAYARAN DIGITAL (DIGITAL PAYMENT) BERBASIS APLIKASI OVO DI KOTA PEKANBARU BERDASARKAN PERATURAN BANK INDONESIA NO.18/40/2016 TENTANG PENYELENGGARAAN PEMROSESAN TRANSAKSI PEMBAYARAN - Hastuti, Ester Widi; Deliana, Evi; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In this information age, consumer behavior began to change a lot. In conducting a transaction, they now prioritize payment systems for ease, flexibility, efficiency and simplicity. Bank Indonesia as the organizer of transaction activities also actively encourages the emergence of various types of non-cash payments such as checks, billboards, demand deposits, ATM cards, debit cards, credit cards, and electronic money, one of which is electronic money based on OVO applications issued by PT. Visionet Indonesia and authorized by Bank Indonesia with letter number and permit date No. 19/661 / DK SISTEM PEMBAYARAN / Srt / B dated 7 August 2017. This study aims to find out:This type of research is sociological legal research and this research is descriptive in nature. The data source used in this study is secondary data, namely data obtained from literature such as legal journals, books, and regulations relating to research. This data analysis is done qualitatively and deductively.From the results of this study there are two problems that can be concluded by the author, firstly, a form of legal protection that if there is a violation in the case of OVO Application-based digital payment transactions and secondly the effort that can be taken by the user in the event of a violation or failure in the case of payment transactions. So according to the author, good faith is needed from the organizer regarding the feasibility of clear, correct and honest information regarding the products and payment transaction activities by prioritizing protection for users of payment services as consumers.Keywords: Legal Protection, Digital Payment Transactions, OVO Application